1999
DOI: 10.1111/j.1469-8749.1999.tb00574.x
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of autistic spectrum disorders in children with Down syndrome

Abstract: The aim of the study was to identify the comorbidity of autistic spectrum disorders in a population of children with Down syndrome (DS). All children with DS within a defined population of South Birmingham were identified. The Asperger Syndrome Screening Questionnaire and the Child Autism Rating Scale were completed and diagnosis made according to ICD‐10 criteria following interview and observation. Thirty‐three of 58 identified children completed the measures, four of whom received a diagnosis of an autistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
2
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 29 publications
2
14
2
1
Order By: Relevance
“…This study, with a small sample size, found a frequency of 7% of PDD in DS (Kent et al, 1999). Our result is more than twofold higher than this previous study, maybe due to methodological issues, such as the screening proprieties of ASQ and/or sample size.…”
Section: Dear Editorcontrasting
confidence: 82%
See 2 more Smart Citations
“…This study, with a small sample size, found a frequency of 7% of PDD in DS (Kent et al, 1999). Our result is more than twofold higher than this previous study, maybe due to methodological issues, such as the screening proprieties of ASQ and/or sample size.…”
Section: Dear Editorcontrasting
confidence: 82%
“…Our result is more than twofold higher than this previous study, maybe due to methodological issues, such as the screening proprieties of ASQ and/or sample size. Despite these differences, one might assume that DS is a risk factor for PDD, since the frequencies found in other mental retardation tend to be lower (Capone et al, 2005;Kent et al, 1999). Interestingly, like previous studies (Fombonne, Zakarian, Bennett, Meng, & Mclean-Heywood, 2006), we found no gender differences between groups suggesting that higher male prevalence found in PDD is lacking in DS population.…”
Section: Dear Editorcontrasting
confidence: 60%
See 1 more Smart Citation
“…Although there have been few reports of autism in individuals with Down syndrome, studies have suggested that the association may be more common than generally thought (Ghaziuddin, Tsai, & Ghaziuddin, 1992;Howlin, Wing, & Gould, 1995;Kent, Evans, Paul, & Sharp, 1999;Kent, Perry, & Evans, 1998). Ghaziuddin et al (1992) estimated that for every 100 persons with Down syndrome, 4 or 5 may also have autism.…”
mentioning
confidence: 96%
“…Ghaziuddin et al (1992) estimated that for every 100 persons with Down syndrome, 4 or 5 may also have autism. Rates of autism have ranged across studies from 1 to 11% of the sample depending on the study, its methodology and the autism criteria used (Collacott, Cooper, & McGrother, 1992;Gath & Gumley, 1986;Kent et al, 1999;Myers & Pueschel, 1991). Kent et al (1999) found that 4 of 58 children with Down syndrome between the ages of 6 and 9 met ICD-10 criteria for autism, a rate of 7%.…”
mentioning
confidence: 99%